A Practical Demonstration of Spectrum Sensing for WiMAX Based on Cyclostationary Features - Baldini, Gianmarco; Giuliani, Raimondo; Capriglione, Diego; Sithamparanathan, Kandeepan (IntechOpen, 2012)
None